CHARACTERIZACION AND INCORPORATION OF INDUSTRIAL SiO2 NANOPARTICLES IN TYPE 1 PORTLAND CEMENT - Osorio Anaya, Ana María (2020)
In this research, it was evaluated the size of industrial silicon dioxide nanoparticles (NPs- SiO2), and their influence on mechanical properties such as compression resistance in samples of type 1 Portland cement after their incorporation (4% by weight) in the formation of mortars, according to ASTM C 109. Through the characterization performed by DR-X technique, it was observed that NPs-SiO2 showed an approximate size of 12,1nm ± 0,3nm besides their amorphous nature. Using TEM analysis, measured sizes were between 10 to 20 nm, whereas the hydrodynamic size measured by DLS technique was 11,6nm ± 0,7nm. Because of the addition of 4% wt. of NPs-SiO2 in samples of type 1 Portland cement, an increase of compressive strength of 20,82 kgf/cm2 was obtained after 28 days, compared with samples of type 1 Portland cement without addition of silica nanoparticles.